2009
DOI: 10.1007/s10530-009-9665-3
|View full text |Cite
|
Sign up to set email alerts
|

Predicting establishment success for introduced freshwater fishes: a role for climate matching

Abstract: We modelled data comprising 1,189 successful and 489 failed introduction records for 280 species of freshwater fishes around the world. We found significant variations in establishment success between genera and families. The number of countries where introductions occurred was a significant predictor of the probability a species would establish in at least one country and all species that had been introduced to nine or more countries (46 species) had established at least one exotic population. We also conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
65
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 66 publications
6
65
0
Order By: Relevance
“…In contrast to a climate‐matching scenario with introductions from sources spanning the ancestral latitudinal range, our results suggest that M. polymorpha has undergone evolution in order to re‐establish a latitudinal flowering cline across North America. Biological invasions are predicted to generally involve climate matching, where exotics thrive in climatic conditions similar to those in their native range such as from one Mediterranean region to another (Duncan, Bomford, Forsyth, & Conibear, ; Peterson, ; Thuiller, Lavorel, Araújo, Sykes, & Prentice, ; Bomford, Barry, & Lawrence, ; Petitpierre et al., ). Climate matching is sufficiently important that it is a central criterion in laws controlling introduction of ornamental species in many countries and regions such as Australia, New Zealand and several Pacific Islands (Pheloung, Williams, & Halloy, ; Daehler, Denslow, Ansari, & Kuo, , Rogg, Buddenhagen, & Causton, 2003‐2005).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to a climate‐matching scenario with introductions from sources spanning the ancestral latitudinal range, our results suggest that M. polymorpha has undergone evolution in order to re‐establish a latitudinal flowering cline across North America. Biological invasions are predicted to generally involve climate matching, where exotics thrive in climatic conditions similar to those in their native range such as from one Mediterranean region to another (Duncan, Bomford, Forsyth, & Conibear, ; Peterson, ; Thuiller, Lavorel, Araújo, Sykes, & Prentice, ; Bomford, Barry, & Lawrence, ; Petitpierre et al., ). Climate matching is sufficiently important that it is a central criterion in laws controlling introduction of ornamental species in many countries and regions such as Australia, New Zealand and several Pacific Islands (Pheloung, Williams, & Halloy, ; Daehler, Denslow, Ansari, & Kuo, , Rogg, Buddenhagen, & Causton, 2003‐2005).…”
Section: Discussionmentioning
confidence: 99%
“…Such preventative measures are cheaper and more effective than those performed at later stages of invasions (Leung et al 2002;Hulme 2006). Climatic similarity between native and target regions is considered as a key requirement for the success of invasions (Ficetola et al 2007;van Wilgen et al 2009;Bomford et al 2010, Medley 2010. Therefore species distribution models (SDM), evaluating the relationships between species and climatic features, are often used to assess the potential distribution of invasive organisms and the areas where the risk of invasion is highest.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental suitability for freshwater species clearly depends on the features of their freshwater habitats. However, for both terrestrial and freshwater species, large scale SDM are often based on environmental variables obtained through geographic information systems or remote sensing (e.g., Ficetola et al 2007;van Wilgen et al 2009;Bomford et al 2010). For terrestrial environments, these variables exist at high resolution and over a large part of the globe (Sillero and Tarroso 2010).…”
Section: Introductionmentioning
confidence: 99%
“…() concluded that monsoonal climates were probably widespread in central and northern Australia at least by the mid‐Tertiary. Climate matching (Bomford et al ., , ), niche conservation (Donoghue, ) and, importantly, biome stasis (Crisp et al ., ) would predict that similarity in biomes would have been conducive to the establishment of dispersed taxa, as taxa readily establish in similar biomes but rarely shift biome.…”
Section: Discussionmentioning
confidence: 99%